Structural and Spectroscopic Studies of Pr3+-Doped GdAlO3 - de Souza Oliveira, Higor Henrique [UNESP]; Cebim, Marco Aurelio [UNESP]; da Silva, Alison Abreu [UNESP]; Davolos, Marian Rosaly [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
In this work, GdAlO3:Pr3+ was successfully prepared by the Pechini method at lower temperatures when compared to others methods such as solid-state synthesis and sol-gel process. In accordance to the XRD data, the fully crystalline single-phase GdAlO3 could be obtained at 900 degrees C. Luminescence measurements indicate Gd -> Pr3+ energy transfer. In the emission spectra, the P-3(0) ->(3) H-4 (blue emission) and D-1(2) ->(3) H-4 (red emission) transitions of Pr3+ ions can be observed and the ratio between their intensities depends on the Pr3+ content due to the cross-relaxation phenomenon.
Keywords: Gadolinium compounds; luminescence; praseodymium; scintillation detectors